2022
DOI: 10.18549/pharmpract.2022.4.2748
|View full text |Cite
|
Sign up to set email alerts
|

Supporting and inhibiting factors of accepting COVID-19 booster vaccination in the elderly in north Jakarta, Indonesia

Abstract: Background:The risk of fatal infection and death from Coronavirus disease 2019 (COVID-19) exposure increases in the elderly and those with coexisting illnesses such as cardiovascular disease, diabetes, cancer, obesity, and hypertension. The COVID-19 vaccine's efficacy and safety have been supported by numerous research. However, data from the Ministry of Health of Indonesia revealed that the elderly in North Jakarta had a reclining interest in receiving a booster dose. This research aimed to assess the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
2
2
0
2
Order By: Relevance
“…Contrastingly, our study also illustrated that those with comorbidities were also concerned about possible adverse effects of the vaccine on their chronic disease state and potential interactions with their medication. This is consistent with the findings of an Indonesian study describing similar fears that accounted for a lower uptake of booster vaccinations [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Contrastingly, our study also illustrated that those with comorbidities were also concerned about possible adverse effects of the vaccine on their chronic disease state and potential interactions with their medication. This is consistent with the findings of an Indonesian study describing similar fears that accounted for a lower uptake of booster vaccinations [ 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Further to this, a study in Italy found that physician information on COVID-19 vaccination was significant in parents' decision to have their children vaccinated [39]. This study, along with other studies, demonstrates that healthcare workers are a trusted source of information for participants, and play a role in participants' decision to vaccinate [19,38,40].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Chất lượng truyền thông được định nghĩa là mức độ một cá nhân được cung cấp thông tin kịp thời, tin cậy và hữu ích(Ball, Simões Coelho, & Machás, 2004). Việc tiếp cận với các nguồn thông tin chính thống về vaccine giúp người dân trang bị đầy đủ kiến thức, hiểu đúng về vaccine, xóa bỏ nghi ngờ và từ đó, giúp gia tăng tỷ lệ tiêm chủng(Cokro, Sharon, & Hadiyanto, 2022). Vì vậy, giả thuyết H7 được đề xuất:H7: Chất lượng truyền thông có ảnh hưởng đến Ý định tiêm tăng cường mũi vaccine COVID_19.Phương pháp nghiên cứuBài viết này sử dụng kết hợp phương pháp nghiên cứu định tính và định lượng, khách thể nghiên cứu là người dân địa bàn thành phố Hà Nội, độ tuổi từ 18 trở lên, có hiểu biết về vaccine và đã từng tiêm vaccine COVID_19.…”
unclassified
“…Chất lượng truyền thông được định nghĩa là mức độ một cá nhân được cung cấp thông tin kịp thời, tin cậy và hữu ích(Ball, Simões Coelho, & Machás, 2004). Việc tiếp cận với các nguồn thông tin chính thống về vaccine giúp người dân trang bị đầy đủ kiến thức, hiểu đúng về vaccine, xóa bỏ nghi ngờ và từ đó, giúp gia tăng tỷ lệ tiêm chủng(Cokro, Sharon, & Hadiyanto, 2022). Vì vậy, giả thuyết H7 được đề xuất:H7: Chất lượng truyền thông có ảnh hưởng đến Ý định tiêm tăng cường mũi vaccine COVID_19.Phương pháp nghiên cứuBài viết này sử dụng kết hợp phương pháp nghiên cứu định tính và định lượng, khách thể nghiên cứu là người dân địa bàn thành phố Hà Nội, độ tuổi từ 18 trở lên, có hiểu biết về vaccine và đã từng tiêm vaccine COVID_19.…”
unclassified